Identification of Factors Causing Quiet Quitting in Organizations Based on the Perspective of Literature Studies - Safariyani, Eva; Fadillah, Alan Fajar (Universitas Pamulang, 2025)
The advancement of technology, the era of Industry 4.0, and the COVID-19 pandemic have introduced significant changes in the business world, affecting both organizations and employees. These shifts have contributed to the phenomenon of quiet quitting, where employees reduce their commitment to work without formally resigning. This phenomenon often emerges as a response to burnout, work-life imbalance, and high expectations from employers. This study compiles various research to analyze the contributing factors and negative impacts of quiet quitting on organizations. Findings indicate that quiet quitting is driven by job dissatisfaction, poor communication, lack of career development opportunities, and unsupportive organizational culture. The results highlight the importance of creating a positive work environment, fostering effective communication, and providing career development opportunities to mitigate the adverse effects of quiet quitting. Further research is needed to explore in depth the factors contributing to quiet quitting and to design more effective strategies for its prevention.